Local rainfall is more likely than distant thunderstorms to affect movement behaviour in Northern Kenyan elephants. - Tom Mulder; Beth Mortimer; Jelle Ferwerda; Fritz Vollrath (PLoS ONE)
Previous research indicates that African savanna elephants change their movements preceding or coincident with local rainfall and it has been suggested that they respond to thunder in remote storms-perhaps reading seismic cues. We therefore aimed to test if elephants in Northern Kenya adhere to distinct daytime movement states between the wet and dry periods, and whether their abrupt movement changes precede local wet periods in response to lightning strikes from a specific compass heading. In our study site, lightning to the North and East often preceded local rainfall and could possibly be used to anticipate local wet periods, but local rainfall appears a more likely trigger of behavioural change. While some abrupt movement changes occurred ahead of local wet periods, they were only particularly frequent shortly following the onset of wet periods. These findings do not concur with reports of Namibian elephants that generally changed their movement behaviour preceding local rainfall, and the additional exploration of individual behaviours in the present study likewise did not provide compelling evidence of a generic reliance on remote thunder cues by Northern-Kenyan elephants. Nonetheless, the GPS tracks of elephants indicated that daytime movement velocities differed between wet and dry periods. Specifically, elephants were generally in a slow-moving state during the day through wet periods, and in a fast-moving state during the day through dry periods. There is a further indication that some elephants compensated for slow daytime speeds by moving faster at night. This shift towards increased nocturnal activity may become more common with climate change and may slightly reduce elephant foraging efficiency. We conclude that climate change makes a strong case for studying elephant behaviours in response to environmental cues during the day and night, especially in dry-land study sites like Northern Kenya.